Sosialisasi Advertising Dan Pemasaran Digital UMKM Pengrajin Pot Bunga Di Desa Mekargalih Jatiluhur Purwakarta - Kristianto, Rio; Komariah, Kokom; Jalaludin, Jalaludin (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the economic and industrial growth of a country. Especially with the current technological advances, it is easy for MSME players to introduce and sell their products widely. Digital marketing is one of the main keys to being able to carry out online transaction activities, both using social media and marketplaces. Due to the lack of knowledge about digital marketing and advertising, it is difficult for business actors to develop and compete. In community service activities carried out in Mekargalih Village, it aims to enable MSME players to expand product sales and encourage the economic growth rate of flower pot industry players so as not to lose market share. The community service activities that have been carried out can be concluded that the process of socializing advertising and digital marketing has a positive impact on the business development of flower pot craftsmen. Starting from increasing the knowledge of business actors about the use of internet technology as an online marketing medium, increasing the ability and skills of business actors in building and running online marketing and until flower pot craftsmen are able to expand the product sales network nationally and even internationally. The program to support community service activities also has a positive impact on the community, because the community feels helped and provides awareness of the importance of maintaining cleanliness, especially maintaining the cleanliness of places of worship such as prayer rooms, jami'mosques and mejlis ta'lim. In addition, the community also feels helped by the Al-Quran waqf program, because the existence of a new and readable Al-Quran can increase interest in continuing to read the Al-Quran.